Optimization Control SK Box Manoeuvres For GEO Satellites using Electric Thrusters (Ocskbox) (Global Journal of Science Frontier Research, 2015)
Abstract not found
Keywords: geostationary satellites; SKBOX; box-limit; electric propulsion; specific impulse; quadratic programming